Hydrothermal synthesis of Li co-doped Zn0.98Mg0.02O nanoparticles and their structural, optical and electrical properties. Issue 9 (July 2016) - Senol, S.D.; Erdem, M.
Abstract: Zn0.98− x Mg0.02 Li x O ( x =0.0, 0.01, 0.02, 0.03) nanoparticles were synthesized by the hydrothermal method. The structural, optical and electrical properties of the samples were analyzed by X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Diffuse Reflectance UV–vis spectroscopy, and Hall effect measurements. XRD results showed that Zn0.98− x Mg0.02 Li x O with wurtzite structure are obtained without impurities and additional phases. The lattice parameters ( a, c ) initially decrease, but they increase with further Li doping. The optical measurements exhibited blue-shift of optical band edge and widening of the band gap. Temperature dependent transport measurements using Van der Pauw method showed that Li doping increased the resistivities and charge carrier density, while it decreased the Hall mobility.